Upaya Meningkatkan Minat Belajar Siswa dalam Mata Pelajaran Pendidikan Agama Islam Menggunakan Metode Role Playing Kelas X SMK N 1 Ampek Angkek - Rahmi, Asyfida; Sari, Eriza Rahma; Monia, Fenny Ayu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to determine efforts to increase students' interest in learning in Islamic religious education subjects using the role playing method. This research uses a qualitative approach or case study approach method. Researchers obtained data through direct observation and interviews. The research location was carried out at SMK Negeri 1 Ampek Angkek, Agam Regency for 3 months starting from 13 August - 13 November 2023. Based on the results of observations made, there was a) lack of student interest in studying Islamic Religious Education. b) Efforts to increase students' interest in learning, namely: Teachers look at students' learning styles or ways that suit their needs or habits, Teachers provide several questions that will be answered by students, Teachers provide educational games to students which aim to increase students' enthusiasm for learning, Through methods In this Role Playing, teachers really try to adapt students' learning methods using this method. c) The supporting factor for students' interest in learning is that teachers carry out practice and not only study in the classroom but also in the library, prayer room and others. d) Factors inhibiting students' interest in learning are lack of motivation or support from parents, lack of interest in studying PAI material because students are more focused on their respective major subjects.